Effect of two different habitats on spine and gonad colour in the purple sea urchin Paracentrotus lividus. (14th February 2014) - Addis, Piero; Moccia, Davide; Secci, Marco
Abstract This study investigates the effect of different Mediterranean habitats on spine and gonad colouring and gonadal index in the purple sea urchin Paracentrotus lividus (Echinodermata: Echinoidea). Specimens were collected in winter 2012 in Posidonia oceanica meadows and rocky bottom areas at two sites in Southern Sardinia (Italy, Tyrrhenian Sea). Colorimetric analyses of spines and gonads were conducted with a digital colorimeter using CIELAB colour spaces, which defines the colour in terms of three coordinate values: lightness (L*), redness (a*) and yellowness (b*). Lightness and redness of the spines differed significantly between habitats, whereas colour spaces of the gonads did not. A careful analysis of the gonad index showed it to be significantly affected by habitat, registering higher values in rocky bottom locations. In conclusion, it seems that habitat does affect spine colour but not gonad colour. Spine colour seems to be site‐dependent, whereas the gonad index depends solely on the habitat.